PROFIL PENGKAJIAN RESEP OBAT HIPERTENSI PADA PASIEN RAWAT JALAN RSUD LAPATARAI KABUPATEN BARRU - Rosdiana, Rosdiana; Nurlina, Nurlina; Aztriana, Aztriana (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
The prevalence of hypertension sufferers in Indonesia and even in the world continues to increase, causing an crease in the number of prescriptions for antihypertensive meds in hospitals and also the possibility of an increase in errors in prescribing antihypertensive cure This study aims to examine the completeness of antihypertensive as medicine prescriptions including administrative reviews, pharmaceutical studies, and clinical studies in outpatients from October to December 2022 at the Lapatarai Hospital, Barru District. The method in this research is descriptive with the type of research retrospective. From this study, it was found that there were 99 prescription sheets containing antihypertensive meds. The results of the assessment of the study showed that 100% of the prescriptions did not include the patient's address, the patient's weight, the patient's height, the patient's allergy history and the doctor's SIP number. In the pharmaceutical study, it was found that 100% of the prescriptions wrote down the dosage form, dosage strength, and instructions for using the medicine. With the majority of antihypertensive meds prescribed in tablet dosage forms. In terms of clinical requirements, it was found that the prescriptions were not duplicated and there were 95,38% of prescriptions that had conection between antihypertensive as medicine recipe and other meds supplies. The results of this study show a discrepancy between the review profile of antihypertensive as medicine recipe at the Lapatarai general hospital by standard regulations in Indonesia.